N-type hanging polycrystalline material resistivity grading method

Through the calculation and conversion of the deposition theory, the resistivity of the N-type hanging polycrystalline material is accurately solved, and the problem of large resistivity test deviation in the straight-pull single crystal process is improved, and the accuracy of the grading and electrical performance stability are improved.

CN119530952APending Publication Date: 2025-02-28HONGYUAN NEW MATERIAL BAOTOU CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411579295.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the straight-pull single crystal process, the resistivity test deviation during the flow process of the N-type lifting polycrystalline material is large, resulting in uneven cross-sections, a lot of fragments, and difficulty in resistivity testing, which affects the resistivity concentration of the crystal rod.

Method used

Through the calculation of the decondensation theory, the N-type hanging polycrystalline material is calibrated and divided into the resistance value range by the amount of the leftover material of the output bay, calculate the impurity concentration corresponding to the remaining amount of the output bay of the lift polycrystalline material, convert the resistivity of the current concentration, and reversely push the resistance of the lift polycrystalline material range to achieve accurate grading.

Benefits of technology

The concentration of resistivity of N-type hanging polycrystalline materials has been improved, the accuracy of grading is improved, the hit rate has been increased by 12.32%, reducing resistance abnormalities and improving the stability of non-standard material electrical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530952A_ABST
    Figure CN119530952A_ABST
Patent Text Reader

Abstract

The invention discloses an N-type hanging polycrystal material resistivity grading method, which comprises the following operation steps: in a straight pulling single crystal process, especially when an N-type circulating material is processed, the resistivity of the material is known and controlled, the resistivity is the measure of the hindering degree of the material to current flow and is influenced by the doping concentration and the temperature, and the resistivity of the material is determined according to the influence of the doping concentration and the temperature. And estimating the resistivity when the corresponding residual material amount grows through the initial head resistivity, the doping concentration and the segregation coefficient in the growth process. According to the resistivity grading method for the N-type hanging polycrystal material, the resistance value range of the N-type hanging polycrystal material is calibrated and divided according to the crucible remaining quantity of an output furnace platform through segregation theory measurement and calculation, the impurity concentration corresponding to the residual quantity of the output furnace platform of the hanging polycrystal material is calculated, and the resistivity corresponding to the current concentration is converted to obtain the tail resistance of the hanging polycrystal material; and the resistor in the range of the suspended polycrystal material is reversely pushed, so that the suspended polycrystal material can be accurately graded, and the resistivity concentration ratio is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of Czochralski single crystals, and in particular to a resistivity grading method for N-type hanging polycrystalline materials. Background Art

[0002] The resistivity grading method for N-type hanging polycrystalline material is a method for resistivity testing and control in the circulation process of N-type hanging polycrystalline material. In the CZ single crystal process, especially when processing N-type circulating material, it is very important to understand and control the resistivity of the material. Resistivity is a measure of the degree of resistance of the material to the flow of current. It is affected by doping concentration, temperature and other factors. During the growth or processing of single crystals, the distribution of dopants in the crystal may change through the phenomenon of segregation, thereby affecting the resistivity. With the continuous development of science and technology, people have higher and higher requirements for the manufacturing process of the resistivity grading method for N-type hanging polycrystalline material.

[0003] At present, the N-type hanging polycrystalline material in the industry is easily broken during the circulation process and when the surface is polished to measure the resistivity, resulting in uneven cross-section and many broken materials. It is difficult to use a portable resistance meter to test the resistivity and the deviation is large, resulting in abnormal resistivity sorting of each gear of the hanging polycrystalline material, large output resistivity fluctuations and extremely low hit rate, which affects the resistivity concentration of the crystal rod and brings certain adverse effects to people's use process. To this end, we propose a resistivity grading method for N-type hanging polycrystalline material. Summary of the invention

[0004] Technical problem to be solved: In view of the shortcomings of the prior art, the present invention provides a resistivity grading method for N-type hanging polycrystalline material. The resistance value range of N-type hanging polycrystalline material is calibrated and divided according to the amount of crucible left in the production furnace through the fractionation theory. The impurity concentration corresponding to the amount of remaining material on the production furnace of the hanging polycrystalline material is calculated, and the resistivity corresponding to the current concentration is converted to obtain the tail resistance of the hanging polycrystalline. The range resistance of the hanging polycrystalline material is inferred, and the hanging polycrystalline material can be accurately graded to improve the resistivity concentration, which can effectively solve the problems in the background technology.

[0005] Technical solution: To achieve the above purpose, the technical solution adopted by the present invention is: a resistivity grading method of N-type hanging polycrystalline material, comprising the following steps: S1: In the CZ single crystal process, especially when processing N-type recycled materials, the resistivity of the material is understood and controlled. Resistivity is a measure of the degree of resistance of the material to the flow of current and is affected by doping concentration and temperature. S2: During the growth or processing of single crystals, the distribution of dopants in the crystal may change through the segregation phenomenon, thus affecting the resistivity. The resistivity when the corresponding amount of residual material is grown is estimated by the initial head resistivity and doping concentration and the segregation coefficient during the growth process; S3: Segregation refers to the phenomenon of uneven distribution of solutes between the solid phase and the liquid phase. During the growth of a single crystal, if the solubility of the dopant in the solid phase and the liquid phase is different, the concentration of the dopant in the crystal will change during the growth process; S4: The resistance value range of the N-type hanging polycrystalline material is divided according to the amount of crucible left in the output furnace by the segregation theory, and the impurity concentration corresponding to the amount of residual material on the output furnace of the hanging polycrystalline material is calculated; S5: Convert the current concentration corresponding resistivity to get the tail resistance of the hanging polycrystalline, and reversely calculate the range resistance of the hanging polycrystalline material, so as to accurately divide it into grades.

[0006] As a preferred technical solution of the present application, the change of doping concentration is estimated in the steps S4 and S5, and the change trend of resistivity is estimated accordingly, so that the suspended polycrystalline material can be accurately graded and the resistivity concentration can be improved.

[0007] As a preferred technical solution of the present application, the S1-S5 steps improve the N-type hanging polycrystalline material flow process. Due to the large deviation in resistivity test, it is easy to break when the surface is polished to measure the resistivity, resulting in uneven cross-section and difficult resistivity testing of broken materials with large deviation.

[0008] As a preferred technical solution of the present application, the hit rate in the S1-S5 steps is improved, and the accuracy of N-type hanging polycrystalline material grading is improved. The hit rate of hanging polycrystalline material is increased by 12.32% compared with the same period, and the resistivity concentration is improved.

[0009] As a preferred technical solution of the present application, the steps S1-S5 improve the electrical performance stability of non-standard materials and reduce electrical performance defects caused by resistance anomalies.

[0010] As a preferred technical solution of the present application, the concentration is converted into resistivity in step S2: .

[0011] As a preferred technical solution of the present application, in the steps S1-S5, the resistivity after growth is estimated by the initial head resistivity, doping concentration and segregation coefficient during the growth process, and the impurity concentration corresponding to the remaining material on the polycrystalline material production furnace is calculated by the remaining material on the polycrystalline material production furnace. The current concentration is converted to the corresponding resistivity to obtain the resistance of the polycrystalline tail, and the resistance range of the polycrystalline material is inferred.

[0012] As a preferred technical solution of the present application, the dopant in the step S3 is one of phosphorus and arsenic used for N-type doping.

[0013] Beneficial effects: Compared with the prior art, the present invention provides a resistivity grading method for N-type hanging polycrystalline materials, which has the following beneficial effects: the resistivity grading method for N-type hanging polycrystalline materials divides the resistance value range of N-type hanging polycrystalline materials according to the amount of crucible left in the output furnace through the fractionation theory, calculates the impurity concentration corresponding to the amount of residual material on the output furnace of the hanging polycrystalline materials, converts the current concentration corresponding to the resistivity to obtain the tail resistance of the hanging polycrystalline, reversely infers the range resistance of the hanging polycrystalline materials, and then the hanging polycrystalline materials can be accurately graded, and the resistivity concentration is improved; The N-type hanging polycrystalline material circulation process has a large deviation in resistivity testing. It is easy to break when the surface is polished to measure the resistivity, resulting in uneven cross-section, difficult resistivity testing and large deviation. Improve the hit rate and the accuracy of N-type hanging polycrystalline material grading. The hit rate of hanging polycrystalline material has increased by 12.32% compared with the same period, and the resistivity concentration has been improved. Improve the electrical performance stability of non-standard materials and reduce electrical performance defects caused by resistance abnormalities. The entire N-type hanging polycrystalline material resistivity grading method has a simple structure, is easy to operate, and has better results than traditional methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The overall process schematic diagram of a resistivity grading method for N-type hanging polycrystalline material according to the present invention. DETAILED DESCRIPTION

[0015] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0016] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0017] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0018] like Figure 1 As shown, a resistivity grading method for N-type hanging polycrystalline material includes the following steps: S1: In the CZ single crystal process, especially when processing N-type recycled materials, the resistivity of the material is understood and controlled. Resistivity is a measure of the degree of resistance of the material to the flow of current and is affected by doping concentration and temperature. S2: During the growth or processing of single crystals, the distribution of dopants in the crystal may change through the segregation phenomenon, thus affecting the resistivity. The resistivity when the corresponding amount of residual material is grown is estimated by the initial head resistivity and doping concentration and the segregation coefficient during the growth process; S3: Segregation refers to the phenomenon of uneven distribution of solutes between the solid phase and the liquid phase. During the growth of a single crystal, if the solubility of the dopant in the solid phase and the liquid phase is different, the concentration of the dopant in the crystal will change during the growth process; S4: The resistance value range of the N-type hanging polycrystalline material is divided according to the amount of crucible left in the output furnace by the segregation theory, and the impurity concentration corresponding to the amount of residual material on the output furnace of the hanging polycrystalline material is calculated; S5: Convert the current concentration corresponding resistivity to get the tail resistance of the hanging polycrystalline, and reversely calculate the range resistance of the hanging polycrystalline material, so as to accurately divide it into grades.

[0019] Furthermore, in steps S4 and S5, the change of doping concentration is estimated, and the change trend of resistivity is estimated accordingly, so that the polycrystalline material can be accurately graded and the resistivity concentration can be improved.

[0020] Furthermore, in steps S1-S5, the flow process of N-type hanging polycrystalline material is improved because the resistivity test deviation is large and the surface is easily broken when the resistivity is measured, resulting in uneven cross-section and difficult resistivity testing of broken materials with large deviation.

[0021] Furthermore, the hit rate in steps S1-S5 is improved, and the grading accuracy of N-type hanging polycrystalline materials is improved. The hit rate of hanging polycrystalline materials is increased by 12.32% compared with the same period, and the resistivity concentration is improved.

[0022] Furthermore, in steps S1-S5, the electrical performance stability of non-standard materials is improved, and electrical performance defects caused by resistance anomalies are reduced.

[0023] Furthermore, the concentration in step S2 is converted into resistivity: .

[0024] Furthermore, in steps S1-S5, the resistivity after growth is estimated by the initial head resistivity, doping concentration and segregation coefficient during the growth process, and the impurity concentration corresponding to the remaining material on the polycrystalline material production furnace is calculated by the remaining material on the polycrystalline material production furnace. The current concentration is converted to the corresponding resistivity to obtain the resistance of the polycrystalline tail, and the resistance range of the polycrystalline material is inferred.

[0025] Furthermore, the dopant in step S3 is one of phosphorus and arsenic for N-type doping.

[0026] In the CZ process, especially when dealing with N-type recycled material, it is very important to understand and control the resistivity of the material. Resistivity is a measure of the degree to which the material hinders the flow of electric current, and it is affected by doping concentration, temperature and other factors. During the growth or processing of the single crystal, the distribution of dopants in the crystal may change through the phenomenon of segregation, which affects the resistivity. The resistivity when growing the corresponding amount of residual material can be estimated by the initial head resistivity and the doping concentration and the segregation coefficient during the growth process.

[0027] Introduction to segregation phenomenon: Segregation refers to the phenomenon of uneven distribution of solutes between the solid phase and the liquid phase. During the growth of a single crystal, if the solubility of the dopant (such as phosphorus, arsenic, etc. for N-type doping) in the solid phase and the liquid phase is different, the concentration of the dopant in the crystal will change with the growth process.

[0028] Example: Crucible capacity (KG) Theoretical resistance range (head resistivity 1.30Ω.cm) Center resistance (Ω.cm) >550 >1.126 1.18 400-550 0.936-1.126 1.03 300-400 0.796-0.936 0.86 200-300 0.630-1.796 0.71 100-200 0.420-0.630 0.52 <100 <0.420 0.39 The above is the resistivity range classification table The resistivity after growth (or "leftovers") can be estimated by the initial head resistivity, doping concentration, and segregation coefficient during the growth process. The impurity concentration corresponding to the amount of leftovers from the polycrystalline material output furnace is calculated by the amount of leftovers from the polycrystalline material output furnace, and the current concentration corresponding resistivity is converted to obtain the tail resistance of the polycrystalline material, and the range resistance of the polycrystalline material is inferred, and then the polycrystalline material can be accurately graded. However, it is not direct to calculate the resistivity directly through the segregation coefficient, because the relationship between the resistivity and the amount of crucible left is nonlinear, but the change in doping concentration can be estimated, and the trend of resistivity change can be estimated accordingly, so that the polycrystalline material can be accurately graded and the resistivity concentration can be improved.

[0029] It should be noted that, in this article, relational terms such as first and second (number one, number two), etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "including one..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0030] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A resistivity grading method for N-type hanging polycrystalline material, characterized in that: The steps include: S1: In the CZ single crystal process, especially when processing N-type recycled materials, the resistivity of the material is understood and controlled. Resistivity is a measure of the degree of resistance of the material to the flow of current and is affected by doping concentration and temperature. S2: During the growth or processing of single crystals, the distribution of dopants in the crystal may change through the segregation phenomenon, thus affecting the resistivity. The resistivity when the corresponding amount of residual material is grown is estimated by the initial head resistivity and doping concentration and the segregation coefficient during the growth process; S3: Segregation refers to the phenomenon of uneven distribution of solutes between the solid phase and the liquid phase. During the growth of a single crystal, if the solubility of the dopant in the solid phase and the liquid phase is different, the concentration of the dopant in the crystal will change during the growth process; S4: The resistance value range of the N-type hanging polycrystalline material is divided according to the amount of crucible left in the output furnace by the segregation theory, and the impurity concentration corresponding to the amount of residual material on the output furnace of the hanging polycrystalline material is calculated; S5: Convert the current concentration corresponding resistivity to get the tail resistance of the hanging polycrystalline, and reversely calculate the range resistance of the hanging polycrystalline material, so as to accurately divide it into grades.

2. A resistivity grading method for N-type hanging polycrystalline material according to claim 1, characterized in that: In the steps S4 and S5, the change of doping concentration is estimated, and the change trend of resistivity is estimated accordingly, so that the polycrystalline material can be accurately graded and the resistivity concentration can be improved.

3. The resistivity grading method of N-type hanging polycrystalline material according to claim 1, characterized in that: In the steps S1-S5, the N-type hanging polycrystalline material circulation process is improved. Due to the large deviation in resistivity test, it is easy to break when the surface is polished to measure the resistivity, resulting in uneven cross-section, multiple broken materials, and difficult resistivity testing with large deviation.

4. The resistivity grading method of N-type hanging polycrystalline material according to claim 1, characterized in that: The hit rate in the S1-S5 steps is improved, and the grading accuracy of N-type hanging polycrystalline materials is improved. The hit rate of hanging polycrystalline materials is increased by 12.32% compared with the same period, and the resistivity concentration is improved.

5. The resistivity grading method of N-type hanging polycrystalline material according to claim 1, characterized in that: In the steps S1-S5, the electrical performance stability of non-standard materials is improved, and electrical performance defects caused by abnormal resistance are reduced.

6. The resistivity grading method of N-type hanging polycrystalline material according to claim 1, characterized in that: The concentration in step S2 is converted into resistivity: 。 7. The resistivity grading method of N-type hanging polycrystalline material according to claim 1, characterized in that: In the steps S1-S5, the resistivity after growth is estimated by the initial head resistivity, doping concentration and segregation coefficient during the growth process, and the impurity concentration corresponding to the remaining material on the polycrystalline material output furnace is calculated by the remaining material on the polycrystalline material output furnace. The current concentration is converted to the corresponding resistivity to obtain the resistance of the polycrystalline tail, and the resistance range of the polycrystalline material is inversely deduced.

8. The resistivity grading method of N-type hanging polycrystalline material according to claim 1, characterized in that: The dopant in step S3 is one of phosphorus and arsenic for N-type doping.